The implementation of concept-oriented reading instruction in a grade five public elementary class : a case study - KEMBELL, LENTEJAS (Archīum Ateneo, 2013)
This exploratory case study mainly focused on the process of Concept-Oriented Reading Instruction (CORI), its feasibility and application in a local setting. It also determined what effects, if any, CORI had on reading comprehension and reading engagement